Regulating the Natural Resources in the Antarctic Region: A Historical Review - Basberg, Bjørn L (The political economy of resource regulation : an international and comparative history, 1850-2015, 2019)
Keywords: Antarktis; Sørishavet; hvalfangstindustri; hvalindustri; naturressurser; pelagisk; økonomi

Did a Dutch company kill whales with tax payers' money after world war II? - Bruijn, Jaap R; Schokkenbroek, Joost C A (Whaling and History IV : papers presented at a symposium in Sandefjord on the 20th and 21st of June 2013, 2013)
Keywords: Nordmenn; Sørishavet; historie; hvalfangst; pelagisk; sjøfolk

Oral sources at the whaling museum: from speech to text and exhibition - Garmel, Hanne (Whaling and History IV : papers presented at a symposium in Sandefjord on the 20th and 21st of June 2013, 2013)
Keywords: Nordmenn; Sørishavet; erindringer; hvalfangst; museer; pelagisk

Cetus soveticus: exotic and collective cultures of Soviet whaling within the 1960s - Jones, Ryan Tucker (Whaling and History IV : papers presented at a symposium in Sandefjord on the 20th and 21st of June 2013, 2013)
Keywords: Nordmenn; Sørishavet; hvalfangst; pelagisk

Whaling, lobbying and politics - Ringstad, Jan Erik (Whaling and History IV : papers presented at a symposium in Sandefjord on the 20th and 21st of June 2013, 2013)
Keywords: Antarktis; Sørishavet; hvalfangstindustri; hvalindustri; pelagisk; politikk

The friend who outstayed his welcome? Johan Hjort and the difficulties of bringing science to bear upon whaling - Roberts, Peder (Whaling and History IV : papers presented at a symposium in Sandefjord on the 20th and 21st of June 2013, 2013)
Keywords: Sørishavet; fiskeripolitikk; forskning; hvalbestanden; hvalfangst; pelagisk

Whalers' wives in Vestfold, Norway during the pelagic period - Garmel, Hanne (Whaling and History III : papers presented at a symposium in Sandefjord on the 18th and 19th of June 2009, 2010)
Keywords: Norge; Sørishavet; hvalfangst; kulturhistorie; pelagisk

Who owns the history of whaling? The norwegian whaling industry and the writing of modern whaling history - Ringstad, Jan Erik (Whaling and History III : papers presented at a symposium in Sandefjord on the 18th and 19th of June 2009, 2010)
Keywords: Norge; Sørishavet; hvalfangst; kulturhistorie; pelagisk

Helse og helbred sønnafor verden. Litt om legetjenester og helsetilstand blant hvalfangere - Ringstad, Jan Erik (Mdisinhistorie til sjøs, 2008)
Keywords: Sørishavet; helsevesenet; hvalfangere; hvalfangst; pelagisk

Hvalfangerselskapet Kosmos - Boye, Tore (Anders Jahres pengebinge, 2005)
Keywords: Sørishavet; hvalfangstindustri; hvalfangstselskaper; hvalindustri; pelagisk

Økonomi og økologi i ishavene - Kjeldstadli, Knut (Et splittet samfunn : 1905-1935, 2005)
Keywords: Norge; Sørishavet; hvalfangst; pelagisk; økologi; økonomi

”Admiralen” til Sydishavet – et 100 års minne - Ringstad, Jan Erik (Kulturminner, 2005)
Den 21. oktober 1905 forlot flytende kokeri Admiralen og hvalbåtene Ornen og Hauken Sandefjord med kurs for Falklandsayene og Syd Shetland. Dermed innledes et nytt kapittel i den moderne hvalfangsts histone. lnitiativtaker var Christen Christensen, hovedaksjoner og disponent for Aktieselskabet "Ørnen" som eide skipene det første norske hvalfangstselskap som uttrykkelig ble startet for eventuelt innkjøp av et dampskip for innredning til koker.
Keywords: Sørishavet; historie; hvalfangstselskaper; oppdagelsesreiser; pelagisk

Whalers, explorers and scientists: historical perspectives on the development of the antarctic whaling industry - Basberg, Bjørn L (Antarctic challenges : historical and current perspectives on Otto Nordenskjöld's Antarctic expedition 1901-1903, 2004)
Keywords: Carl Anton Larsen; Norge; Sørishavet; ekspedisjoner; forskning; historie; hvalfangere; hvalfangst; pelagisk; polarområdene

Flytende fabrikker – de norske hvalkokeriene - Bernhardt, Pernille Brastad (Fabrikken, 2004)
Keywords: Nordmenn; Sørishavet; arbeidsforhold; historie; hvalfangstindustri; hvalindustri; hvalkokerier; kulturhistorie; pelagisk; sjøfolk

På hvalfangst under sovjetstjernen - Børresen, Dag Ingemar (Arbeiderhistorie, 2004)
Keywords: Nordmenn; Norge; Sørishavet; arbeiderbevegelse; arbeidsforhold; historie; hvalfangst; pelagisk; sjøfolk

Den første norske oljealderen - Elstad, Åsa (Norsk polarhistorie, 2004)
Keywords: Sørishavet; ekspedisjoner; hvalfangstindustri; hvalolje; pelagisk

"Havfruer" og sjøkvinner - Elstad, Åsa (Kystkvinner i Norge, 2004)
Keywords: Norge; Sørishavet; Vestfold; hvalfangst; kulturhistorie; pelagisk

Ein grådig fangstnasjon? - Elstad, Åsa; Finstad, Bjørn-Petter (Norsk polarhistorie, 2004)
Keywords: Sørishavet; hvalfangstselskaper; hvalindustri; hvalolje; kulturhistorie; pelagisk; politikk; økonomi

Antarctica - Sale, Richard (To the ends of the Earth : the history of Polar exploration, 2002)
This text provides an insight into the early history of the Polar regions, and tells the stories of Man's first exploration of the Arctic and Antarctic, and subsequent expeditions. The history of individual Polar expeditions has been told many times, but usually only as personal accounts of individual adventures. This misses the overall context of polar exploration - why the British depended on ponies, or plant-eating animals (on the only continent where plants don't grow), why Franklin's men perished when the local Eskimos were eking out an existence around them (and reporting Franklin's demise), and why the Scandinavians were always better than anybody else. The first map of Antarctica was produced in 1556 - the Vikings visited the Arctic 1,000 years before. In 2001, the US Base at the South Pole is manned 365 days a year. The book tells the whole story of how the two last wildernesses, at either end of the world, were discovered, conquered and tamed.
Keywords: Antarktis; Belgica ekspedisjon; Carsten Egeberg Borchgrevink; Nordmenn; Norge; Roald Amundsen; Southern Cross; Sydpolsekspedisjonen; ekspedisjonen; historie; hvalfangst; oppdagelsesreiser; pelagisk; polareksspedisjoner

Havforskning i tung sjø - Schwach, Vera (Havet, fisken og vitenskapen: fra fiskeriundersøkelser til havforskningsinstitutt 1860-2000, 2000)
Keywords: Sørishavet; forskning; historie; hvalfangst; pelagisk

C.A. Larsen - Pioneer of the Antarctic ocean - Devig, Thor N (Norwegian maritime explorers and expeditions : over the past thousand years, 1999)
Keywords: Antarktis; Carl Anton Larsen; Nordmenn; Sørishavet; historie; hvalfangst; kartlegging; oppdagelsesreiser; pelagisk; polarekspedisjoner

Søylegangen i Buenos Aires - Fløgstad, Kjartan (Eld og vatn : nordmenn i Sør-Amerika, 1999)
Keywords: Antarktis; Carl Anton Larsen; Nordmenn; Roald Amundsen; hvalfangere; hvalfangstindustri; oppdagelsesreiser; pelagisk

Den første olje - Jenssen, Hugo Lauritz (Ambra : Sandefjordmuseene årbok, 1999)
Keywords: Norge; Sørishavet; historie; hvalfangere; hvalfangst; pelagisk; sjøfolk

“Convergence or National Styles? The Japanese Challenge to the British-Norwegian Hegemony in the Twentieth-Century Whaling Industry” - Basberg, Bjørn L (Global Markets: The Internationalization of the Sea Transport Industries since 1850, 1998)
Keywords: Antarktis; Svend Foyn; fiskeindustri; hvalfangst; hvalfangstindustri; hvalfangstnæring; hvalindustri; pelagisk; økonomi

To hvalfangstentreprenøren - to strategier? - Basberg, Bjørn L (I det lange løp : essays i økonomisk historie tilegnet Fritz Hodne, 1997)
Keywords: Antarktis; Carl Anton Larsen; Christen Christensen; Norge; Sørishavet; historie; hvalfangstindustri; hvalfangstselskaper; hvalfangststasjoner; hvalkokerier; næringsliv; pelagisk; økonomi

Norwegian Antarctic whaling seen through the eye of the camera - Barr, Susan (Whaling and history : perspectives on the evolution of the industry, 1993)
Keywords: Norge; Sørishavet; fotografi; historie; hvalfangere; hvalfangst; hvalfangststasjoner; hvalkokeri; pelagisk

Survival against all odds? Shore station whaling at South Georgia in the Pelagic. Era, 1925-1960 - Basberg, Bjørn L (Whaling and history : perspectives on the evolution of the industry, 1993)
Keywords: Norge; Sørishavet; hvalfangere; hvalfangst; hvalfangststasjoner; hvalkokeri; pelagisk; økonomi; økonomisk historie

Oppfinere og teknologisk utvikling i norsk hvalfangsthistorie - Basberg, Bjørn L (Sandefjordmuseene. Årbok, 1986)
Keywords: Antarktis; Nordmenn; Norge; harpuner; historie; hvalfangere; hvalfangst; hvalfangstindustri; hvalindustri; patenter; pelagisk

Moderne hvalfangst. Fra provinsnæring til internasjonal storindustri - Wexelsen, Einar; Møller, Vilhelm (Sandar : grend og gård 1850-1970, med tidsbilder fra næringsliv og kulturhistorie, 1985)
Keywords: Sørishavet; Vestfold; hvalfangere; hvalfangstindustri; hvalindustri; kulturhistorie; pelagisk

Eventyret om hvalfangsten - Christensen, Nils Steen; Hagelund, Olav (Stokke bygdebok, 1983)
Keywords: Nordmenn; Sørishavet; Vestfold; arbeidsforhold; hvalfangere; hvalfangst; pelagisk

Hvalfangst i Sørishavet - Pedersen, Arne Fevang (Kampen på havet : en krigsseilers beretning, 1980)
Keywords: Sørishavet; biografier; erindringer; historie; hvalfangere; hvalfangst; pelagisk

Co-operative Negotiations and Bargaining: Some Notes on Power and Powerlessness - Midgaard, Knut (Power and political theory : some European perspectives, 1976)
Keywords: Norge; Sørishavet; historie; hvalfangst; hvalfangstkvoter; internasjonal; pelagisk; politikk

Internasjonale konferanser - Hva har de ført til? - Kyst-Norge], [Aksjon; Brox, Ottar (Kampen om havet, 1974)
Keywords: Sørishavet; havrett; hvalfangst; hvalfangstkvoten; internasjonal; jus; pelagisk; politikk

Hvalfangst - Wasberg, Gunnar Christie (red.) (Sandar bygdebok, 1968)
Keywords: Sørishavet; Vestfold; historie; hvalfangere; hvalfangstindustri; hvalindustri; pelagisk

Den moderne hvalfangst - Weyergang-Nielsen, Arthur (Larviks historie, 1963)
Keywords: Sørishavet; historie; hvalfangst; pelagisk

Hvalfangst - Weyergang-Nielsen, Arthur (Larviks historie, 1963)
Keywords: Nordmenn; Sørishavet; Vestfold; historie; hvalfangere; hvalindustri; pelagisk

Whaling - Petersen, Kaare (The saga of Norwegian shipping : an outline of the history, growth and development of a modern merchant marine, 1955)
Keywords: Norge; Sørishavet; historie; hvalbåter; hvalfangst; pelagisk; sjøfart; skipsfart

Nitti års norsk hvalfangst - Bogen, Hans (Norge på havet, 1954)
Keywords: Roald Amundsen; Sydpolsekspedisjonen; Sørishavet; historie; hvalfangere; hvalfangstindustri; hvalfangstselskaper; hvalindustri; pelagisk; skipsfart

Whaling - Paulsen, Harald B (Industries of Norway : technical and commercial achievements, 1952)
Keywords: Sørishavet; hvalfangstindustri; næringsliv; pelagisk

Hvalfangerne kommer. Sammenslutningen med radiotelegrafistene. En stormakt på havet - Zachariassen, Aksel (Fra trellekår til frie menn : Norsk sjømannsforbund gjennom 40 år, 1950)
Keywords: Norge; Sørishavet; fagforeninger; historie; hvalfangere; hvalfangstindustri; hvalindustri; pelagisk; sjømenn

Fangsten i nord og syd - Høeg, Ths. Arbo (Larviks sjømannsforening 1849-1949 og byens skibsfart i samme tidsrum, 1949)
Keywords: Sørishavet; Vestfold; historie; hvalfangst; hvalfangstselskaper; pelagisk

Del IV: Hvalfangst - fangstnæring - Knudtzon, Hans Thomas (Norsk fiskeri- og fangsthåndbok : saltvannsfiskeriene : ferskvannsfiskeriene : ishavsfangsten : hvalfangsten, 1949)
Keywords: Sørishavet; fiskerier; historie; hvalfangere; hvalfangst; hvalfangstindustri; hvalfangstkvoter; hvalfangstregulering; hvalfangstselskaper; hvalindustri; internasjonal; næring; pelagisk; samarbeid; økonomi

Hvalfangst på sydfeltet i krigstiden - Vikestad, Arne (Tusen norske skip : en antologi over norske sjøfolks innsats i den annen verdenskrig, 1948)
Keywords: Nordmenn; Sørishavet; Verdenskrigen 1939-45; ekspedisjoner; erindringer; hvalbåter; hvalfangst; pelagisk

Fra Spitsebergisen til Sydhavsbrisen - Stavseth, Reidar (Arven fra Bjørn Farmann : Tønsberg Sjømannsforening gjennom 100 år, 1946)
Keywords: Nordmenn; Sørishavet; historie; hvalfangst; pelagisk; sjøfolk

Fischerei und Fang - Johnsen, Oscar Albert (Norwegische Wirtschaftsgeschichte, 1939)
Keywords: Sørishavet; hvalfangst; pelagisk; økonomi

Wal und Walfischfang - Hjort, Johan (Polarbuch : neue Forschungsfahrten in Arktis und Antarktis mit Luftschiff, U-Boot, Schiffen und Forschungsschiff, 1933)
Keywords: Sørishavet; ekspedisjoner; hvalfangst; pelagisk

Hvaler og hvalfangst - Hjort, Johan (Fra planteverden og dyreliv, 1931)
Keywords: Sørishavet; historie; hvalbestanden; hvalfangstindustri; pelagisk

Skibstyper - Bergh-Smith, Sverre; Jensen, J M (Sjømannsboken : sjøfart, hvalfangst, marine : orientering i sjømannsskap, veiledning til selvstudium, 1930)
Keywords: Sørishavet; hvalfangstindustri; hvalindustri; hvalkokerier; pelagisk; skipsfart; teknologi

Om hval og hvalfangst - Risting, Sigurd (Sjømannsboken : sjøfart, hvalfangst, marine : orientering i sjømannsskap, veiledning til selvstudium, 1930)
Keywords: Sørishavet; historie; hvalfangstindustri; hvalindustri; pelagisk

Fangst og forskning i Sydishavet - Aagaard, Bjarne (Hvalfangsten med tilknyttede næringer, 1929)
Keywords: Carl Anton Larsen; Lars Christensen; Norge; Sørishavet; historie; hvalfangere; hvalfangst; pelagisk

Hval og hvalfangst - Risting, Sigurd (Den Norske sjøfarts historie : fra de ældste tider til vore dage, 1929)
Keywords: Norge; Sørishavet; historie; hvalfangere; hvalfangst; hvalfangstindustri; hvalindustri; pelagisk; skipsfart

Om hval og hvalfangst - Risting, Sigurd (Hvalfangsten med tilknyttede næringer, 1929)
Keywords: Norge; Sørishavet; historie; hvalfangere; hvalfangst; næringsliv; pelagisk

Moderne hvalfangst - Sørlle, Petter (Hvalfangsten med tilknyttede næringer, 1929)
Keywords: Norge; Sørishavet; historie; hvalfangere; hvalfangstindustri; pelagisk

Part II : Whaling South - Morley, Frank Vigor; Hodgson, J S (Whaling north and south, 1927)
Keywords: Norge; Sørishavet; hvalfangere; hvalfangst; norsk; pelagisk

The last phase of whaling - Jenkins, J Travis (A history of the whale fisheries : from the Basque fisheries of the tenth century to the hunting of the finner whale at the present date, 1921)
Keywords: Norge; Sørishavet; historie; historikk; hvalfangere; hvalfangst; pelagisk

Paa fangst i Sydishavet - Nielsen, Eivind (Sjømænd : norske Sjømænds Oplevelser : samlet fra Folkemunde og gjenfortalt, 1896)
Keywords: Carl Anton Larsen; Jason (skip); Sørishavet; ekspedisjoner; hvaler; hvalfangst; oppdagelsesreiser; pelagisk